Treatment of anticoagulated patients with negative pressure wound therapy - Boxall, S.; Carville, K.; Leslie, Gavin; Jansen, S. (Wiley-Blackwell Publishing Ltd, 2017)
© 2017 John Wiley & Sons Ltd and Medicalhelplines.com Inc.There is a paucity of evidence surrounding the use of negative pressure wound therapy (NPWT) in patients receiving anticoagulant medication. Guidelines generally recommend caution regarding the use of NPWT in anticoagulated patients in general, but areas of particular risk are frequently not highlighted. The US Food and Drug Authority (FDA) reported six mortalities between 2009 and 2011 in patients receiving NPWT. These mortalities were associated with the use of NPWT over vascular graft sites. The coagulation status of these patients was not reported. It is the authors' recommendation that guidelines regarding the use of NPWT in anticoagulated patients highlight specific clinical situations of risk, although there is insufficient evidence to support the avoidance of NPWT in anticoagulated patients in general.